Trade Specialization in Latin America: The Impact of China and India - Lederman, Daniel; Olarreaga, Marcelo; Rubiano, Eliana (2012)
This paper examines the extent to which the growth of China and India in world markets is affecting the patterns of trade specialization in Latin American (LA) economies. We construct a measure of Revealed Comparative Advantage (RCA) by 3-digit ISIC sector, country, and year. This RCA accounts for both imports and exports. The empirical analyses explore the correlation between the RCAs of LA and the two Asian economies. Econometric estimates suggest that the specialization pattern of LA--with the exception of Mexico--has been moving in opposite direction to the trade specialization pattern of China and India. Labor-intensive sectors (both unskilled and skilled) probably have been negatively affected by the growing presence of China and India in world markets, while natural resource and scientific knowledge intensive sectors have probably benefited from China and India's growth since 1990.